1982
DOI: 10.1068/p110427
|View full text |Cite
|
Sign up to set email alerts
|

Visual Masking: A Unified Approach

Abstract: The suppression effect observed in masking is assumed to be due to neural inhibition between two stimuli that interact spatially or within a narrow span of time in the fashion demonstrated in simultaneous brightness-contrast experiments. Three principles are brought together in a comprehensive mathematical model of visual masking. The three principles are: lateral inhibition, the integrated visual response function (VRF), and stimulus decay after its offset over a limited period of time (up to about 100 ms). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…This expression of lateral inhibition is what most models of visual masking deal with, which raises an interesting point. Francis (2000) found that four widely discussed models of masking produce nonmonotone performance functions because the strong target signal blocks the effect of the mask at brief SOAs (Anbar & Anbar, 1982;Bridgeman, 1977Bridgeman, , 1978Francis, 1997;Weisstein, 1968Weisstein, , 1972. Clearly, the present experiments, with black-on-white masks and targets, do not rely on mask blocking to produce nonmonotone backward masking, distinguishing our account from many of the bestknown explanations of visual backward masking.…”
Section: Related Ideasmentioning
confidence: 75%
“…This expression of lateral inhibition is what most models of visual masking deal with, which raises an interesting point. Francis (2000) found that four widely discussed models of masking produce nonmonotone performance functions because the strong target signal blocks the effect of the mask at brief SOAs (Anbar & Anbar, 1982;Bridgeman, 1977Bridgeman, , 1978Francis, 1997;Weisstein, 1968Weisstein, , 1972. Clearly, the present experiments, with black-on-white masks and targets, do not rely on mask blocking to produce nonmonotone backward masking, distinguishing our account from many of the bestknown explanations of visual backward masking.…”
Section: Related Ideasmentioning
confidence: 75%
“…These include models by Weisstein (1968Weisstein ( , 1972, Bridgeman (1971Bridgeman ( , 1978, and Anbar and Anbar (1982). Each of these models has previously been used to account for many other aspects of masking (see, e.g., Francis & Hermens, 2002).…”
Section: Model Analysismentioning
confidence: 99%
“…There are a variety of computational models that account for the existence of both U-shaped and monotonicshaped masking functions (Anbar & Anbar, 1982;Bridgeman, 1971Bridgeman, , 1978Francis, 1997Francis, , 2003Weisstein, 1972). Francis (2000) identified a simple computational principle that accounts for the appearance of a U-shaped masking function and showed that this principle is used by all of these models.…”
Section: U-shaped Backward Maskingmentioning
confidence: 99%